2018
DOI: 10.1016/j.otsr.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of patient-specific guided implantation of the glenoid component in reversed shoulder arthroplasty

Abstract: Level 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
3
17
0
2
Order By: Relevance
“…No study has evaluated the accuracy of 3D planning alone using standard instruments without PSI in the setting of RTSA. Our results are comparable to those of Verborgt et al 15 who utilized PSI and planning where they were able to get within 5 of planning and we were able to get within 6 of planning on average. Although larger sample sizes and confirmation of our results by other centers will be necessary to make firm conclusion, based upon our results 3D planning alone is reasonable to accurately place the baseplate even in the setting of severe erosions in the coronal and axial planes requiring bone grafting.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…No study has evaluated the accuracy of 3D planning alone using standard instruments without PSI in the setting of RTSA. Our results are comparable to those of Verborgt et al 15 who utilized PSI and planning where they were able to get within 5 of planning and we were able to get within 6 of planning on average. Although larger sample sizes and confirmation of our results by other centers will be necessary to make firm conclusion, based upon our results 3D planning alone is reasonable to accurately place the baseplate even in the setting of severe erosions in the coronal and axial planes requiring bone grafting.…”
Section: Discussionsupporting
confidence: 87%
“…In the setting of RTSA, 3D computer planning using standard instrumentation without PSI has not been clinically evaluated. Verborgt et al 15 determined that the mean deviation of baseplate version and inclination from the planned version and inclination was on average 4 -5 in a series of patients who underwent RTSA with 3D planning and intraoperative PSI. Dallalana et al 16 also reported deviations of baseplate inclination and version from the planned inclination and version using patient specific guides on average of 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Humphrey et al 14 performed a cadaveric study analyzing screw orientation using both fixed-angle and variable-angle baseplates and reported that 4 of 10 fixed-angle baseplates positioned the superior screw near the suprascapular nerve compared with 0 of 10 variable-angle baseplates. In addition to variable-angle baseplates, new technologies are available to improve rTSA screw positioning and/or length, including 3-dimensional preoperative planning, 15 , 19 , 26 patient-specific glenoid instruments, 12 , 23 , 41 , 42 and intraoperative computer navigation 6 , 21 , 26 , 40 , 42 . If used correctly, these new technologies can also ensure screw placement in the “scapular safe zone” as described by Shishido and Kikuchi 36 to avoid the suprascapular nerve and artery.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative planning and use of patient-specific guides can help improve implant positioning 1419 and reduce the risk of complications resulting from malpositioning. Software can be of great help in preoperative planning and creating patient-specific guides.…”
Section: Introductionmentioning
confidence: 99%